Manajemen Pengelolaan Sampah Pertanian dan Rumah Tangga Di Desa Kaliprau Kecamatan Ulujami Kabupaten Pemalang - Prasetyo, Heru Eko; Muspriyadi, Ribut; Muspriyadi, Amsar (Perigel: Jurnal Penyuluhan Masyarakat Indonesia, 2024)
Kaliprau Village, Ulujami District, Pemalang Regency was declared as a Tourism Village and its location is very strategic. The life of the people is very heterogeneous and full of life dynamics, especially in responding to every development of life and livelihood, some of the population is in the Agricultural Sector. Household women in Kaliprau Village enthusiastically welcomed the agricultural and household waste management management training. The hope is that they will get skills and